Biosynthesis of Iron Nanoparticles by Microorganisms: Characterization and Effects on Human Keratinocytes - López Venditti, Eliana D; Bustos, Pamela S.; Calienni, María Natalia; Montanari, Jorge; Páez, Paulina L.; Paraje, María G.; Guiñazú, Natalia L. (2021)
Metallic nanoparticles (NPs) can be obtained by biosynthesis using microorganisms, as bacteria. Iron is abundant in nature, an essential metal for humans, and a suitable candidate for NPs synthesis with possible microbicidal activity. In this work we biosynthesized iron NPs (FeNPs) and studied possible toxic effects in the human keratinocyte cell line HaCaT. FeNPs were synthesized using Escherichia coli (ATCC 25922), characterized by UV-Vis spectroscopy and by transmission electron microscopy. HaCaT cells were incubated for 4 and 24 h at different FeNPs concentrations (535; 214, 107, 53.5 and 26.75 𝜇g/ml). Controls: culture medium, metal precursor salt solution FeSO4 (0.1 and 0.25 mM), and bacterial growth control of biosynthesis (CCB, dilutions 1/2, 1/5, 1/10, 1/20, 1/40). We investigated cell viability by MTT and neutral red test (NRT), reactive oxygen species (ROS) by DCF-DA and by NBT, superoxide dismutase (SOD) activity by the riboflavin-NBT method, and glutathione (GSH) content by the Ellman method. FeNPs had a spherical shape with an average size of ≈ 20 nm. Cell viability decreased after 4 and 24 h incubation with FeNPs 535 𝜇g/ml, and CCB 1/2. However, no changes in NRT uptake were observed at 4 and 24 h. The ROS levels were significantly increased after 4 h and 24 h incubation with all the treatments assayed. In addition, O2- production significantly increased at 24 h of incubation with FeNPs 535 𝜇g/ml, and CCB 1/2. SOD activity was increased at all treatments tested. Finally, the GSH content was not modified by any treatment at 24 h. Altogether these results suggest that the highest FeNPs concentration significantly modifies the cell viability with increase in O2-, ROS, and SOD. In contrast, other stimuli were able to modify HaCaT oxidant/antioxidant cell balance, but not cell viability. Prolonged incubation studies are needed in order to determine if cell viability is altered at lower concentrations and to unravel the mechanisms underlying these alterations.
Keywords: Ciencias médicas y de la salud::Biotecnología médica::Biotecnología relacionada con la salud